SERUM ANTIBODY ANALYSIS FOLLOWING HEPATITIS B VACCINATION FOR OCCUPATIONAL RISK ASSESSMENT AMONG DENTAL STUDENTS - Hegde, Shruthi; N., Praveen B.; Pal, Sumona; Shetty, Shishir Ram; Ajila, Vidya; Babu, Subhas; K., Harini (Journal of Health and Allied Sciences NU, 2014)
Background & Objectives: Hepatitis B is the most important infectious occupational disease for the health care workers. Dental surgeons are frequently in contact with blood and saliva and hence are at high risk for Hepatitis B Virus (HBV) exposure. HBV infection is a major public health problem in India, as there are 45 million estimated carriers. Immunization against HBV reduces the risk of transmission of HBV to dental personnel and from dental personnel to patients. The present study was aimed to evaluate the serum levels of anti-HBs in vaccinated dental health care workers.Methods: In this study, estimation of serum levels of Anti- HBs in 40 dental students vaccinated against HBV was done. Data was obtained regarding vaccination data, age, sex, weight, height and smoking history. Anti-HBs level was evaluated two years after the 1st dose of vaccination. Low responders were given booster vaccination and post booster anti HBs assay was done.Results: The study included 110 hepatitis B vaccinated dental students. Out of 110 students only 40 students had documented history of complete vaccination and volunteered to be a part of the study. Among these 40 students, three students (7.5%) had less than 100 IU/L anti–HBs level and 37 students (92.5%) had more than 100 IU/L anti–HBs level. Anti- HBS level above 100 IU/L is identified to be protective. Following booster vaccination, low responders showed anti -HBs titre more than 100 IU/L.Conclusion: In this study majority dental students had desirable immune response to the HBV vaccine. Male gender and positive smoking history could have attributed to low anti-HBs titre in subjects who had inadequate levels in our study. Hence, all Health Care Workers, in particular dental surgeons with contributory factors like smoking habit, male gender should undergo periodic assessment of anti-HBs titre.
Keywords: Anti-HBs; Hepatitis B Virus; Dental Students